Diaconia as the Art of the Possible: Diaconal Engagement for Roma Migrants in Oslo, Norway - Bjørn Hallstein Holte (Religions, 2023)
Itinerant Roma migrants travelling from Eastern European countries have featured across the European Economic Area (EEA) since the European Union’s eastward expansions in 2004 and 2007. Being unskilled, many Roma migrants engage in casual work and street work such as playing music, selling magazines, collecting and recycling bottles and cans, and begging, making them conspicuously visible in countries with public welfare services and low poverty levels. Citizens of EEA countries can enter and stay legally in other countries in the EEA for up to three months, after which they must register as workers or jobseekers, and generally leave. It is well documented how the countries Roma citizens of EEA countries travel to have enacted migration control measures, often in the form of complex and fine-grained regulations, that exclude them from public welfare services. This is also true of the Nordic countries, such as Norway, where they coincide with universalistic welfare states aiming to cover everyone living in their territories with the same benefits and services. In the Nordic countries, as in other countries, service provision for Roma migrants is largely in the hands of non-governmental organisations, many of them diaconal organisations running emergency shelters, soup kitchens, and other humanitarian services to alleviate suffering for people at the margins of the welfare state. The diaconal organisations also engage in case work and advocacy work to ensure the realisation of the Roma migrants’ rights. Many of the organisations depend on public grants, making their relationship to the welfare state ambiguous. This article investigates Christian social practice in the form of diaconal engagement for Roma migrants in Oslo, Norway at the intersection of migration control, the universalistic welfare state, and the theological underpinnings of the organisations.